Efficacy and Adverse Events of Apatinib Salvage Treatment for Refractory Diffuse Malignant Peritoneal Mesothelioma: A Pilot Study - Yang, Zhi-Ran; Su, Yan-Dong; Ma, Ru; Wu, He-Liang; Li, Yan (Frontiers in Oncology, 2022)
Objective To investigate the clinical efficacy and adverse events of apatinib salvage treatment for diffuse malignant peritoneal mesothelioma (DMPM) that has failed to respond to the recommended treatments. Methods 27 patients with refractory DMPM were treated with apatinib at our center from April 2014 to October 2020, at the initial dose of 250 mg/d. The dose was reduced to 125 mg/d when serious adverse events (SAEs) occurred. 28-day was set as a treatment cycle. The frequency of follow up was once every 28 days. The efficacy evaluation was conducted according to the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria and the serum tumor markers before and after apatinib treatment. The safety assessment was performed with the National Cancer Institute (NCI) Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. The primary endpoints were objective response rate (ORR) and disease control rate (DCR), and the secondary endpoints were adverse events (AEs). Results The 27 patients completed a median treatment-cycle of 15.0, ranging from 5.1 to 39.4 cycles. At the median follow-up of 14.3 (4.8-51.8) months, median overall survival (OS) was 59.4 months, median apatinib-treatment-related survival (ATRS) was 14.0 (4.8-36.8) months. Complete response (CR) was observed in 0 case (0.0%), partial response (PR) in 4 cases (14.8%), stable disease (SD) in 12 cases (44.4%), and progression disease (PD) in 11 cases (40.7%). The ORR was 14.8%, and DCR was 59.3%. The median serum CA125 values before and after apatinib treatment were 32.9 (7.0-4592.4) U/mL and 29.7 (6.1-4327.4) U/mL, respectively (P=0.009). The common AEs were hypertension (6/27; 22.2%), hand-foot syndrome (5/27; 18.5%), albuminuria (4/27; 14.8%), anemia (4/27; 14.8%), leukopenia (4/27; 14.8%), rash (2/27; 7.4%), fatigue (2/27; 7.4%), oral ulcers (2/27; 7.4%), hoarseness (2/27; 7.4%), nausea/vomiting (2/27; 7.4%), diarrhea (2/27; 7.4%), headache (1/27; 3.7%), and fever (1/27; 3.7%). The incidence rate of grade III/IV AEs was 16.2%. Conclusions Apatinib is effective in treating refractory DMPM, with promising efficacy and acceptable safety.